Justice League the Darkseid War saga omnibus - Johns, Geoff 1973- (DC Comics, 2017)
"Collected for the first time in its entirety, experience the epic conclusion to Geoff Johns' five-year run on JUSTICE LEAGUE with JUSTICE LEAGUE: THE DARKSEID WAR SAGA OMNIBUS! The Justice League came together to stop the forces of Darkseid from destroying Earth five years ago. Now the ruler of Apokolips returns, but sets his sights on the world-shattering Anti-Monitor. Will the combined might of the Justice League be enough to protect the Earth from the collateral damage as Gods fight? The NEW YORK TIMES best-selling series from Geoff Johns comes to its explosive conclusion here in this massive hardcover! Featuring art from comics industry all-stars including Jason Fabok, Francis Manapul and more"...